Digital Literacies of Report 191 Programme Pre-entry Level Students at a Technical and Vocational Education and Training College in South Africa - Buthelezi, Michael Mbongiseni; Hlalele, Dipane Joseph; Dhlamini, Ntokozo Mazwikayise (Journal of Education and Learning Technology, 2024)
Grounded on connectivism learning theory, the current study concedes that beyond the phases of the digital divide, research has shown that there is still a digital literacy gap among Report 191 programme pre-entry level technical and vocational education and training (TVET) college students that require attention. While TVET college students are expected to possess digital skills, research has indicated that on reaching TVET Colleges, many students do not possess the requisite digital literacies. Using a survey design, this quantitative study explored digital literacies amongst Report 191 programme pre-entry level students at a TVET college in South Africa. Data were analysed using the Statistical Package for the Social Sciences (SPSS, version 22). With a Cronbach Alpha value of 7.6, the instrument was considered valid and reliable. The findings suggested the prevalence of an uneven/diverse digital literacy prowess among Report 191 programme pre-entry level students. Researchers recommended a focused and differentiated programme of digital literacy support for Report 191 programme pre-entry level students at TVET colleges. This study will help all TVET lecturers and policymakers start to acknowledge how ubiquitous digital literacy skills are becoming in educational settings, not just technological ones. Keywords: Digital Literacy, Internet Access, Pre-Entry Level Students, Report 191 Programme, Technological Devices, TVET